HUBUNGAN KECEPATAN LARI 40 YARD DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTERA KELAS VIII SMPN 7 PASIR EMAS KECAMATAN SINGINGI - Agust, Kristi; ', Masrizal; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the low long jump results students of SMPN 7 Pasir Emas. This is presumably because of the 40 yard running speed and explosive power leg muscles. Therefore, the purpose of this study was to determine whether there is a relationship 40 yard running speed and explosive power leg muscles with long jump results squat style male students class VIII of SMPN 7 Pasir Emas. The data were obtained from the 40 yard running tests, explosive power leg muscles test and long jump test squat style. The sample in this study using purposive sampling technique so that the number of samples 15 male students. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. Based on the analysis of data obtained rx1.y amounted to 0.92, and r x2.y amounted to 0.96, rx1x2 of 0.98 and 0.97 with rtabel rx1x2.y 0.514 on significant level α = 0:05. means rcount> rtable, thus hypothesis is: There is a relationship a relationship with a 40 yard running speed long jump results squat style male students of class VIII SMP Negeri 7 Singingi District of Pasir Emas. There is a relationship of leg muscle explosive power with the result of long jump squat style male students of class VIII SMP Negeri 7 Singingi District of Pasir Emas. There is a relationship a relationship 40 yard running speed and explosive power leg muscles with the result of long jump squat style male students of class VIII SMP Negeri 7 Singingi District of Pasir Emas.Keywords : Running Speed 40 yard, Explosive Power Leg Muscles, Long Jump